APPLICATION OF ACTIVE CARBON AND ZEOLITE AS ADSORBEN COMPONENT OF RAPID SAND FILTER (A SIMPLE APPLICATION OF TECHNOLOGY IN DEPURATING FRESH WATER) - Fatahilah Fatahilah; Ismadi Raharjo (Jurnal Zeolit Indonesia, 2007)
Fresh or clean water is a primary need in housing life. Clean water is used in all housing activities starting from daily needs, they are food and drink; healthy needs for example taking a bath, washing and so on, it is included non primary needs for instance watering plant, washing motorcycle or car and etc. By Increasing population growth, housing need is higher so that many simple housing like Rumah Sangat Sederhana, RSS are established in suburb. Sometimes the location of housing is landfill of swam or field area. In Fulfilment of clean water, developer usually establish shallow well. For example Gelora Persada Housing, Rajabasa, Bandar Lampung. The quality of shallow well in farmer swam or field usually have high organic content that produce bad taste and smell, high turbidity, acid (low pH), and contain high iron (Fe) element. In research was conducted in shallow well of Gelora Persada Housing, Rajabasa, Bandar lampung by using rapid sand filter wich is completed by active carbon and zeolite as adsorbance so that gained to decrease turbidity level from 23,9 NTU become 6,51 NTU; can increase pH value from 6,24 to 6,44 and it also can decrease iron (Fe) content from 3,04 mg/lt become 0,74 mg/lt.